What's the score? Do pleural effusion clinical scoring systems help in management of disease? - Grendelmeier, P; Rahman, N (Thieme Publishing, 2019)
Pleural effusion is a common condition, affecting over 3,000 people per million population every year. More than 50 causes of pleural effusions are known, including pleural infection and malignant pleural disease. These conditions place a large burden on healthcare systems with one-fourth of patients with pleural infection having a length of hospital stay of more than 1 month. Malignant pleural effusion represents advanced malignant disease with a correspondingly high mortality. Prognostic models using clinical information in combination with blood or pleural fluid biomarkers predicting survival and other outcome measures are therefore a priority in improving clinical care, and potentially outcomes. Identifying patients with poor prognosis may help avoid discomfort and unnecessary interventions at the end of their lives, while, on the other hand, individuals with scores predicting a particularly good prognosis might be selected for more aggressive early treatment. Such scores must be based on data representing routine practice in a general hospital and variables chosen based on their clinical availability at clinical decision points (i.e., before treatment is instituted), making the findings widely applicable.